Multi-centennial-scale variations of South American summer monsoon intensity in the southern central Andes (24-27°S) during the late holocene - Kock, Sebastian T.; Schittek, Karsten; Mächtle, Bertil; Maldonado, Antonio; Vos, Heinz; Lupo, Liliana C.; Kulemeyer, Julio J.; Wissel, Holger; Schäbitz, Frank; Lücke, Andreas (Geophysical research letters, 2020)
Oxygen isotope records of cushion-plant peat cellulose from the southern central Andes capture evidence for significant environmental changes. We observe that the delta O-18(cell) peatland record from Cerro Tuzgle (24 degrees S) is in high conformity with the respective Lagunillas peatland record (27 degrees S). During the late Holocene, two significant fluctuations occurred and are interpreted as regional moisture signals with increased precipitation amounts indicated during multi-centennial phases from 1,530 to 1,270 cal. yr BP and from 470 to 70 cal. yr BP. These fluctuations can be best explained by changes in the strength of the South American summer monsoon (SASM). This interpretation is further supported by consistency with northern Andean paleoclimate records (10-13 degrees S) and very high correlation (R-2 = 0.76) with the Southern Oscillation Index. The congruent precipitation signals suggest the persistent climatic control of the SASM-strength in this latitudinal band during the last 1,800 years. Plain Language Summary Stable oxygen isotopes (d18Ocell) that are incorporated in cellulose of organic matter of plants accumulated by cushion peatlands on the Puna Plateau are a useful tool to investigate past environmental changes in the southern central Andes. Contemporaneous changes in the composition of delta O-18(cell) became evident in the high-elevation peatlands from Cerro Tuzgle (24 degrees S) and Lagunillas (27 degrees S). Within the last 1,800 years, two distinct fluctuations occurred that can be interpreted as change in the regional precipitation supply which is controlled by the South American summer monsoon (SASM) intensity. According to this interpretation, specifically, high SASM-activity and, thus, increased precipitation occurred between 1,530 to 1,270 cal. yr BP and between 470 to 70 cal. yr BP whereas SASM-strength reduced before 1,530 cal. yr BP and between 1,270 to 470 cal. yr BP. Strong support for this interpretation is the high accordance with other SASM-affected paleoclimatic records of the northern central Andes (10-13 degrees S) and high conformity with the Southern Oscillation Index. This also indicates a persistent impact of the SASM during the last 1,800 years.